2016
DOI: 10.1007/s11051-016-3466-2
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of gold and silver nanoparticles using gallic acid: catalytic activity and conversion yield toward the 4-nitrophenol reduction reaction

Abstract: In the present report, gallic acid was used as both a reducing and stabilizing agent to synthesize gold and silver nanoparticles. The synthesized gold and silver nanoparticles exhibited characteristic surface plasmon resonance bands at 536 and 392 nm, respectively. Nanoparticles that were approximately spherical in shape were observed in high-resolution transmission electron microscopy and atomic force microscopy images. The hydrodynamic radius was determined to be 54.4 nm for gold nanoparticles and 33.7 nm fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 21 publications
4
53
0
2
Order By: Relevance
“…The results obtained of this study are similar to the previous studies that also investigated the UV-vis spectra of AgNPs in the range 350-400 nm [23]. Several studies have confirmed the correlation between the UV-vis spectrum and properties of AgNPs [24][25][26][27]. A single peak in the UV-vis spectrum can be correlated with uniform spherical AgNPs [28][29].…”
Section: Uv-vis Characteristicssupporting
confidence: 89%
“…The results obtained of this study are similar to the previous studies that also investigated the UV-vis spectra of AgNPs in the range 350-400 nm [23]. Several studies have confirmed the correlation between the UV-vis spectrum and properties of AgNPs [24][25][26][27]. A single peak in the UV-vis spectrum can be correlated with uniform spherical AgNPs [28][29].…”
Section: Uv-vis Characteristicssupporting
confidence: 89%
“…In this green process, oxidation reaction of phenol groups in gallic acid is responsible for silver ions reduction (Additional file 1 : Figure S1). Then, produced quinoid compounds with a ketoenol-system are adsorbed on the surface of silver nanoparticles accounting for its stabilization [ 36 , 37 ]. Additionally, gallic acid molecules on the surface of nanoparticles form hydrogen bonds between neighboring molecules further stabilizing the AgNPs [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Excellent reviews were reported by the author about the utilization of plant extracts and polysaccharides in the green synthesis of AuNPs and AgNPs [12]. We have used plant extracts (Artemisia capillarys [13], Leonurus japonica [14], Polygala tenuifolia [15,16], Caesalpinia sappan [17,18], Bupleurum falcatum [19], and Galcinia mangostana [20]), invertebrate animal extracts (Eisenia andrei and Achatina fulica) [21], pure compounds from plant origins (resveratrol [22], tannic acid [23,24], rosmarinic acid [25], caffeic acid [26], chlorogenic acid [27], gallic acid [28] and catechin [29]) and pure compounds from animal origins (heparin [30], chondroitin sulfate [31,32], acharan sulfate [31] and sialyllactose [33]). Medicines, such as ampicillin [34], vancomycin [35] and ethambutol [36], were also utilized as reducing agents.…”
Section: Introductionmentioning
confidence: 99%